A new genetic architecture for PHS resistance in rice: deciphering the epistatic interactions of three major QTL - Lee, Chang-Ju; Kim, Tae-Heon; Baek, Dong-Hyun; Gao, Jingli; Park, Woo-Geun; Kim, Suk-Man (Frontiers in Plant Science, 2026)
Pre-harvest sprouting (PHS), the premature germination of grains before harvest, threatens rice yield and quality under erratic climatic conditions. This study aims to investigate the genetic basis of PHS resistance by conducting a genome-wide association study (GWAS) on 182 diverse rice genetic resources representing multiple ecotypes using 289,569 high-quality single-nucleotide polymorphisms. Three major QTLs—qRPH7, qRPH8, and qRPH11—were identified using the complementary multi-locus models, Bayesian information and Linkage disequilibrium, iteratively Nested Keyway and Multi-Locus Mixed Model. qRPH7 showed the strongest association, explaining up to 80% of phenotypic variance, and co-localized with SDR4 and qPH7. Allelic combination analyses revealed that the qRPH7–SDR4 and qRPH7–qPH7 combinations conferred strong resistance, whereas qRPH7 alone was insufficient. In contrast, qRPH11 contributed additively to enhance resistance, while qRPH8 displayed antagonistic epistasis that reduced resistance stability. Overall, PHS resistance is governed by a polygenic architecture involving both additive and epistatic interactions. These findings establish a new genetic architecture underlying PHS resistance in rice and propose a targeted breeding strategy through pyramiding qRPH7 with SDR4, qPH7, and qRPH11. This study advances mechanistic insight into seed dormancy and sprouting while providing actionable resources to support marker-assisted selection and accelerate the development of PHS-resistant cultivars suited to climate change.